Locative Inversion and Stage Topics: A Cross-Linguistic Study - Joana Teixeira (Discours)
This paper seeks to identify the conditions which a clause-initial X phrase (XP) must satisfy to license locative inversion. Three SVO (subject-verb-object) languages with distinct degrees of word order flexibility are considered: English, French and European Portuguese (EP). We show that these languages only permit locative inversion with preposed XPs which are stage topics (sTOPs), i.e. presupposed XPs that define a (spatio-temporal) location. We further show that being a sTOP is both a necessary and sufficient condition for an XP to license this type of inversion. In addition to the structures typically classified as locative inversion, cases of “absolute inversion” in French, “free” inversion in sentence-focus contexts in EP, and inversion structures with preposed participial and adjectival phrases in English and French are argued to be licensed by (c)overt sTOPs and, thus, constitute forms of (covert) locative inversion. We conclude that there is a strong correlation between sTOPs and subject-verb inversion cross-linguistically.